Evaluasi Penempatan SDM Kesehatan di Puskesmas melalui Studi Kasus dan Analisis Fishbone - Puri Rohmatulloh (Universitas La Tansa Mashiro, 2024)
Human resource management is an important component in ensuring effective health services, especially in regional areas such as Rangkasbitung, Lebak Regency, Banten Province. Despite various decentralization efforts, disparities in the distribution and utilization of health workers remain a problem. At the Rangkasbitung Public Health Center (UPT Puskesmas), shortages of personnel and inappropriate staff placement remain major challenges. The ratio of healthcare workers to the population is insufficient to meet service needs, thereby impacting the quality of healthcare services for the community. This study aims to evaluate the human resource management system related to workforce placement through a descriptive qualitative approach. Data analysis was conducted using a fishbone diagram to identify the root causes based on four factors: man (competence and number of personnel), method (procedures and human resource monitoring), material (facilities, infrastructure, and medical equipment), and money (budget constraints). The results of the study indicate systemic issues in aligning staff expertise with assigned tasks, exacerbated by insufficient training, inadequate facility support, and budget constraints. To address these issues, the study recommends improvements in HR allocation policies, efficiency in sub-district health budgets, regular training for healthcare workers, and infrastructure upgrades. These strategies aim to